Production of biogas via anaerobic digestion from coconut copra waste and cow manure - Abd. Hamid, Mohd. Kamaruddin (2015)
Anaerobic digestion is a common process for the treatment of a variety of organic wastes and biogas production. Both, macro and microalgae are suitable renewable substrates for anaerobic digestion process. In this paper, the production of biogas, mainly methane from coconut copra and cow manure was experimentally investigated using anaerobic digestion method. In addition, the mix of coconut copra and cow manure as a feedstock was also studied. The yeast which acts as a catalyst was used and added to the sample to accelerate the anaerobic process. Batch anaerobic digester was used with the incubation of 8 days and operational temperature in a range of 30-320C. From the Gas Chromatography Thermo Conductivity Detector (GC-TCD) analysis, the biogas produced from anaerobic digestion of coconut copra waste produces 6.22% methane (CH4) and 40.55% carbon dioxide (CO2). While for the cow manure, the yields of CH4 and CO2 were 14.51% and 36.07%, respectively. For the mixed sample, the yield of CH4 and CO2 was 8.40% and 31.2%.